Intraoperative Rupture of the Ovarian Capsule in Early-Stage Ovarian Cancer: A Meta-analysis. Issue 2 (August 2021) - Dioun, Shayan; Wu, Jenny; Chen, Ling; Kaplan, Samantha; Huang, Yongmei; Melamed, Alexander; Gockley, Allison; St. Clair, Caryn M.; Hou, June Y.; Tergas, Ana I; Khoury-Collado, Fady; Machida, Hiroko; et al.
Abstract : OBJECTIVE: To examine the effects of intraoperative ovarian capsule rupture on progression-free survival and overall survival in women who are undergoing surgery for early-stage ovarian cancer. DATA SOURCES: MEDLINE using PubMed, EMBASE (Elsevier), ClinicalTrials.gov, and Scopus (Elsevier) were searched from inception until August 11, 2020. METHODS OF STUDY SELECTION: High-quality studies reporting survival outcomes comparing ovarian capsule rupture to no capsule rupture among patients with early-stage epithelial ovarian cancer who underwent surgical management were abstracted. Study quality was assessed with the Newcastle-Ottawa Scale, and studies with scores of at least 7 points were included. TABULATION, INTEGRATION, AND RESULTS: The data were extracted independently by multiple observers. Random-effects models were used to pool associations and to analyze the association between ovarian capsule rupture and oncologic outcomes. Seventeen studies met all the criteria for inclusion in the meta-analysis. Twelve thousand seven hundred fifty-six (62.6%) patients did not have capsule rupture and had disease confined to the ovary on final pathology; 5, 532 (33.7%) patients had intraoperative capsule rupture of an otherwise early-stage ovarian cancer. Patients with intraoperative capsule rupture had worse progression-free survival (hazard ratio [HR] 1.92, 95% CI 1.34–2.76, P <.001), with moderate heterogeneity (I 2 =41%, P =.07) when compared with those without capsule rupture. Pooled results from these studies showed a worse overall survival (HR 1.48, 95% CI 1.15–1.91, P =.003), with moderate heterogeneity (I 2 =53%, P =.02) when compared with patients without intraoperative capsule rupture. This remained significant in a series of sensitivity analyses. CONCLUSION: This systematic review and meta-analysis of high-quality observational studies shows that intraoperative ovarian capsule rupture results in decreased progression-free survival and overall survival in women with early-stage ovarian cancer who are undergoing initial surgical management. SYSTEMATIC REVIEW REGISTRATION: PROSPERO, CRD42021216561. Abstract : Intraoperative ovarian capsule rupture is associated with shorter progression-free survival and overall survival than no rupture among women with early-stage ovarian cancer who are undergoing initial surgical management.